The Impact of Project-Based Learning on Students’ Creativity in Visual Arts Education - Kamolova E’zoza Iskandar qizi (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article explores the significance of project-based learning (PBL) in visual arts education and its role in enhancing students’ creative competencies. Drawing on the research of Shovdirov S. A. and other contemporary scholars, the paper demonstrates how PBL encourages independent thinking, problem-solving, and interdisciplinary integration. The study highlights strategies for implementing PBL effectively, including digital technologies, interactive methods, and collaborative projects, creating an engaging and student-centered learning environment.